Mindfulness as the Fundamental Element in Developing Effective Communication Between Late Adolescents and Parents - Tampubolon, Merryana Kurnia; Yusuf, Syamsu; Dahlan, Tina Hayati (International Journal of Education, 2021)
The purpose of this article is to explain the fundamental element that helps develop effective communication between parents and late adolescents. While undergoing academic activities in higher education, late adolescents often experience various academic stresses. To deal with these, late adolescents need to communicate with their parents as their closest relatives. This way, they can get positive support to be more motivated and responsible in academic activities. Late adolescents - parents good communication may also reduce learning burnout and depression. However, the types of communication that occurred are not as expected. It does not provide the right solutions, and it makes late adolescents feel judged, unrespected and even causes conflicts. Therefore, parents and adolescents need to know the fundamental element to develop effective communication between them. Through literature review as the preliminary research conducted to determine what elements can develop effective communication, findings showed that mindfulness is the fundamental element in developing effective communication between parents and their late adolescents who are experiencing academic stress in higher education.